State Policy in the Field of Video Games: Approaches and Prospects - Sergey N. Fedorchenko (RUDN Journal of Political Science)
The objective of the article is to identify the most pertinent approaches and prospects for state policy in the field of video games. The author’s methodological perspective includes the principles of critical discourse analysis of academic works, comparative study of case studies, and scenario techniques. The author discusses the liberal, conservative, and hybrid approaches to state video game policy. The author also underlines the difference between active and reactive video game policies. The identified approaches, issues, prospects, and aspects are updated in terms of their relevance to present Russian state policy tasks. The study also aims to define the ecumenical paradigm of state sovereignty. The importance of collaboration between the state, developer representatives, and the player community in regulating the industry and the video game market is emphasized. The author’s grasp of the political industrial phenomenon helps to describe the opportunities and risks of such contact. To better comprehend the prospects for the transition of Russian state video game policy, basic development scenarios are described.